Transformational leadership, professional learning communities, teacher learning and learner centred teaching practices; Evidence on their interrelations in Mozambican primary education. (March 2019) - Luyten, Hans; Bazo, Manuel
Highlights: Impact of transformational leadership studied through structural equation modelling. Effect of transformational leadership on teaching practice strong but indirect. Effect of learning communities on teaching practice both direct and indirect. Transformational leadership and learning communities important in African context. Abstract: This study examines the routes via which transformational leadership, professional learning communities and teacher learning lead to more learner centred teaching practices. By means of structural equation modelling (path analysis with latent variables) a conceptual model was tested, using questionnaire data from 518 teachers in 95 Mozambican primary schools. The data analysis shows that the effect of transformational leadership on teaching practices is substantial but indirect, running via professional learning communities and teacher learning. All in all, the impact of professional learning communities on teaching practices is particularly strong. Its effect is both direct and indirect, running via teacher learning. The findings show the relevance of the concepts transformational leadership and professional learning communities in an African context.